PENGARUH PEMBERIAN PENGUATAN (REINFORCEMENT) GURU TERHADAP MOTIVASI BELAJAR SISWA SD KEMALA BHAYANGKARI 1 - Amelia Ratih Damayanti; Suharmono Kasiyun; Nafiah Nafiah; Sri Hartatik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to analyze the provision of teacher strengthening, learning motivation, and to determine the effect of giving reinforcement teachers on student’s learning motivation SD Kemala Bhayangkari 1 Surabaya. The subjects of this study were students in grades II, III, IV and V with 77 students. This type of research used quantitative descriptive with correlation methods. The technique of collecting data used a questionnaire. The instrument has been validated by expert lecturers in the field of education and by using SPSS calculations. The data was analyzed by using descriptive analysis and non-parametric statistics with Spearman rank correlation test analysis. The results showed that giving teachers’ reinforcement was included in the quite good category with 45.45%, the students’ motivation in learning was included in the good category with 46.75%, the effect of giving reinforcement and learning motivation has a positive and significant effect between teachers reinforcement on learning motivation of SD Kemala Bhayangkari 1 Surabaya. The findings showed that the results of the Spearman rank correlation test on the correlation coefficient value was 0.578 with a significant level value of 0.01 (0.578 > 0.01) while the value of sig. of 0.00 with a significant level of 0.01 (0.00 < 0.01). Giving teachers’ reinforcement on learning motivation was included in the moderate category at a correlation coefficient of 0.578 (0.40 - 0.599).